Ameloblastic fibro-odontoma with chondroid tissue formation - Aly, Noura; Amer, Hatem; Khatib, Omar El (Contemporary Oncology/Współczesna Onkologia, 2018)
Ameloblastic fibro-odontoma (AFO) is an uncommon, benign, mixed odontogenic tumour occurring predominantly in children and adolescents. The purpose of this study was to report an unusual case of AFO in the mandible of a five-year-old male patient showing evidence of chondroid tissue formation. Clinical, radiographic, histopathological and immunohistochemical findings were presented. Intraoral examination revealed a swelling extending from the right deciduous lateral incisor to the left second molar area. Computed tomography (CT) showed a large, well-demarcated multilocular radiolucency with radiopaque deposits. Histologically, the lesion was composed of connective tissue stroma resembling the dental papilla, with epithelial islands, and amorphous masses of enamel and dentin consistent with a diagnosis of AFO, as well as, evidence of large areas showing cartilaginous tissue formation. Immunohistochemistry using cytokeratin, vimentin and s-100 were helpful in determining the origin of the different odontogenic tissues. Surgical excision of the lesion was performed. The patient has been monitored and the lesion has not recurred. We report the first case of AFO showing an unusual behaviour of chondroid tissue formation.